Developing Telemental Health Partnerships Between State Medical Schools and Federally Qualified Health Centers: Navigating the Regulatory Landscape and Policy Recommendations. Issue 3 (4th October 2018) - Fortney, John C.; Veith, Richard C.; Bauer, Amy M.; Pfeiffer, Paul N.; Valenstein, Marcia; Pyne, Jeffrey M.; Dalack, Gregory W.; Kramer, Teresa L.; Ferro, Lori J.; Metzger, Karla; Shore, Jay H.; Carlo, Andrew D.; et al.
Abstract: Background: Federally Qualified Health Centers (FQHCs) deliver care to 26 million Americans living in underserved areas, but few offer telemental health (TMH) services. The social missions of FQHCs and publicly funded state medical schools create a compelling argument for the development of TMH partnerships. In this paper, we share our experience and recommendations from launching TMH partnerships between 12 rural FQHCs and 3 state medical schools. Experience: There was consensus that medical school TMH providers should practice as part of the FQHC team to promote integration, enhance quality and safety, and ensure financial sustainability. For TMH providers to practice and bill as FQHC providers, the following issues must be addressed: (1) credentialing and privileging the TMH providers at the FQHC, (2) expanding FQHC Scope of Project to include telepsychiatry, (3) remote access to medical records, (4) insurance credentialing/paneling, billing, and supplemental payments, (5) contracting with the medical school, and (6) indemnity coverage for TMH. Recommendations: We make recommendations to both state medical schools and FQHCs about how to overcome existing barriers to TMH partnerships. We also make recommendations about changes to policy that would mitigate the impact of these barriers. Specifically, we make recommendations to the Centers for Medicare and Medicaid about insurance credentialing, facility fees, eligibility of TMH encounters for supplemental payments, and Medicare eligibility rules for TMH billing by FQHCs. We also make recommendations to the Health Resources and Services Administration about restrictions on adding telepsychiatry to the FQHCs' Scope of Project and the eligibility of TMH providers for indemnity coverage under the Federal Tort Claims Act.